An LC–MS/MS method for rapid and sensitive high‐throughput simultaneous determination of various protein kinase inhibitors in human plasma. (12th August 2016) - Abdelhameed, Ali S.; Attwa, Mohamed W.; Kadi, Adnan A.
Abstract: A reliable, high‐throughput and sensitive LC–MS/MS procedure was developed and validated for the determination of five tyrosine kinase inhibitors in human plasma. Following their extraction from human plasma, samples were eluted on a RP Luna®‐PFP 100 Å column using a mobile phase system composed of acetonitrile and 0.01 m ammonium formate in water (pH ~4.1) with a ratio of (50:50, v /v) flowing at 0.3 mL min −1 . The mass spectrometer was operating with electrospray ionization in the positive ion multiple reaction monitoring mode. The proposed methodology resulted in linear calibration plots with correlation coefficients values of r 2  = 0.9995–0.9999 from concentration ranges of 2.5–100 ng mL −1 for imatinib, 5.0–100 ng mL −1 for sorafenib, tofacitinib and afatinib, and 1.0–100 ng mL −1 for cabozantinib. The procedure was validated in terms of its specificity, limit of detection (0.32–1.71 ng mL −1 ), lower limit of quantification (0.97–5.07 ng mL −1 ), intra‐ and inter assay accuracy (−3.83 to +2.40%) and precision (<3.37%), matrix effect and recovery and stability. Our results demonstrated that the proposed method is highly reliable for routine quantification of the investigated tyrosine kinase inhibitors in human plasma and can be efficiently applied in the rapid and sensitive analysis of their clinical samples.